Factors Associated with Mortality in COVID-19 Patients Treated at Serui General Hospital, Papua Indonesia - Fahri Ahmad Baihaqi; Henny Rumaropen (Faculty of Medicine, Universitas Padjadjaran, 2022)
Coronavirus Disease 2019 (COVID-19) has a high fatality rate and has caused around 4,771,408 deaths worldwide as of 30 September 2021. COVID-19 infection presents various severity levels, starting from asymptomatic to severe symptoms that lead to death. Mortality in COVID-19 patients is associated with multiple risk factors. This study aimed to analyze the risk factors associated with COVID-19 mortality in Serui General Hospital, Papua, Indonesia. A cross-sectional analytic observational study was performed in Serui General Hospital from September 2020to September 2021. Subjects were COVID-19 positive inpatients who met the inclusion and exclusion criteria. The independent variables were demographic characteristics, clinical manifestations, comorbidities, and lab findings, while the dependent variable was mortality. Statistical analysis was performed using chi-square test and logistic regression. This study included sixty-nine patients with 21 (30.4%) of them were non-survivors. The multivariate analysis showed that an NLR of >3.13 (OR 7.49; p=0.037; 95% CI 1.63–34.35), hypertension (OR 4.71; p=0.019; 95% CI 1.28–17.29), and age (OR 4.26; p=0.028; 95% CI 1.17–15.52) were associated with mortality in COVID-19 patients. Thus, NLR >3.13, hypertension, and age are considered to be the risk factors associated with the mortality caused by COVID-19 among patients in Serui General Hospital.